2007
DOI: 10.1631/jzus.2007.b0428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1.5% lidocaine and 0.5% ropivacaine epidural anesthesia combined with propofol general anesthesia guided by bispectral index

Abstract: Abstract:Objective: To compare the effects of epidural anesthesia with 1.5% lidocaine and 0.5% ropivacaine on propofol requirements, the time to loss of consciousness (LOC), effect-site propofol concentrations, and the hemodynamic variables during induction of general anesthesia guided by bispectral index (BIS) were studied. Methods: Forty-five patients were divided into three groups to receive epidurally administered saline (Group S), 1.5% (w/w) lidocaine (Group L), or 0.5% (w/w) ropivacaine (Group R). Propof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…However, side effects are inevitable and include irregular heart rate, low blood pressure, burning sensation at the site of injection and suppression of breathing (26). Combined application of epidural anesthesia, such as ropivacaine and lidocaine, may reduce the propofol doses required for the induction and maintenance of anesthesia, and further reduce its side effects in clinical practice (27,28). The present study investigated the effects of propofol and/or ropivacaine on cardiomyocytes in vitro under normoxic or CoCl 2 -induced hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, side effects are inevitable and include irregular heart rate, low blood pressure, burning sensation at the site of injection and suppression of breathing (26). Combined application of epidural anesthesia, such as ropivacaine and lidocaine, may reduce the propofol doses required for the induction and maintenance of anesthesia, and further reduce its side effects in clinical practice (27,28). The present study investigated the effects of propofol and/or ropivacaine on cardiomyocytes in vitro under normoxic or CoCl 2 -induced hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Also, there are multiple studies that have shown that there is a significant reduction in the propofol dose required for induction of anesthesia. [ 1 5 ] BIS is used to measure the depth of anesthesia. We titrated the BIS value to 45–55 to avoid awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation: A study carried out by Xiang and Li. [ 1 ] in 2007 has found that the time to loss of consciousness with propofol in ropivacaine group to be 111 s (standard deviation = 17). Based on the above finding the sample size for the present study was estimated with a relative precision of 6% and desired confidence level of 95%, it was estimated that 30 patients need to be included in ropivacaine group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many reports to reduce propofol injection pain, and combination therapy using various drugs, such as ketamine (Bano et al, 2007;Saadawy et al, 2007), metoprolol (Asik et al, 2003), metoclopramide (Fujii and Nakayama, 2005), bupivacaine (Senturk et al, 2002), dexamethasone (Kwak et al, 2008), remifentanil (Kwak et al, 2007a,b;Roehm et al, 2003), ropivacaine (Xiang and Li, 2007), alfentanil (Fang and Keyes, 2006), dexmedetomidine (Turan et al, 2005) and flurbiprofen (Fujii and Nakayama, 2004) have been suggested for the prevention of propofol pain. Consequently, our results can provide further insight into the physicochemical stability of propofol emulsions containing other drugs, and these data can also help clinical researchers gain a better understanding of propofol's administration in existing applications.…”
Section: Discussionmentioning
confidence: 99%